Arctic geology and petroleum potential : proceedings of the Norwegian Petroleum Society conference, 15-17 August 1990, Troms, Norway - Vorren, T. O. (Norwegian Petroleum Society (NPF) special publication, 1993)
Since the search for hydrocarbon resources in the Arctic started in the 1930's the exploration activity has expanded into many of the Arctic regions, and several of the Arctic sedimentary basins have proven to be important sources of hydrocarbon. Nevertheless, the Arctic continental margins and adjacent onshore areas are still largely unexplored in the context of petroleum, and are therefore considered to be one of the few regions in the world where significant undiscovered sources of hydrocarbon may exist. The aim of the book is to give an updated overview of the geology of the Arctic sedimentary basins and their petroleum potential. Although the different basins vary significantly as regards sedimentary fill and tectonic evolution, many of the basins share some of the characteristics needed to become prolific oil and gas provinces. The book contains 45 extensively illustrated articles. It starts with papers on the Mesozoic source rocks, and oceanic natural gas clatrates in the Arctic, respectively. Then follow articles on the regional and petroleum geology of the main regions; Greenland, North American Arctic, Soviet Arctic and the Barents Sea. Particular emphasis is placed on the Barents Sea. The two last chapters comprise articles on salt dynamics and methods. The book closes with a paper on international law in the Arctic. This volume will be of interest to both students and professional earth scientists/petroleum explorationists working in the northern latitudes. It will allow the readers to stay abreast of the development in this climatic region of the world.